1998
DOI: 10.1038/emm.1998.28
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphism of the CYP1A1 and glutathione-S-transferase gene in Korean lung cancer patients

Abstract: The levels of expressions and catalytic activities of cytochrome P450 (CYP1A1) and glutathione-S-t r a n sferase class (GSTM1) enzymes in lungs and their metabolic balance may be an important determinant host factor underlying lung cancer. Genetic differences in metabolism, MspI restriction sites, Ile-Val polymorphism of CYP1A1 gene, and the null genotype of GSTM1 have been reported to be associated with susceptibility to lung cancer. The present studies were undertaken to establish frequencies of the polymorp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
20
0

Year Published

1999
1999
2009
2009

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(21 citation statements)
references
References 24 publications
1
20
0
Order By: Relevance
“…In a Swedish study (24), neither variant was associated with any subtype of lung cancer. Hong et al (25) reported a significant deficit of the CYP1A1*2C polymorphism in Korean lung cancer cases compared with controls, although notably genotypes were not in HardyWeinberg equilibrium, even in controls, making this result difficult to interpret. Studies of non-Asians conducted in America and Europe have been generally negative with few exceptions (26)(27)(28)(29).…”
Section: Discussionmentioning
confidence: 90%
“…In a Swedish study (24), neither variant was associated with any subtype of lung cancer. Hong et al (25) reported a significant deficit of the CYP1A1*2C polymorphism in Korean lung cancer cases compared with controls, although notably genotypes were not in HardyWeinberg equilibrium, even in controls, making this result difficult to interpret. Studies of non-Asians conducted in America and Europe have been generally negative with few exceptions (26)(27)(28)(29).…”
Section: Discussionmentioning
confidence: 90%
“…There has been one report for genotype frequency of MspI polymorphism in Korean population (Hong et al, 1998). Hong et al (1998) reported a minor allele frequency of 0.3 for MspI polymorphism in a control group consisted with 63 subjects. Therefore, the genotype frequency of this polymorphism among Korean population needs to be confirmed in other studies.…”
Section: Discussionmentioning
confidence: 99%
“…An MspI polymorphic site at the 3′-flanking region of CYP1A1 gene was identified (Kawajiri et al, 1990) and this allele was called CYP1A1*2A (Cascorbi et al, 1996). It has been reported that there is an association between the CYP1A1*2A allele and lung cancer in Japanese, white, Hawaiian and Korean populations (Kawajiri et al, 1990;Xu et al, 1996;Hong et al, 1998;Le Marchand et al, 1998). However, in other studies, using populations such as Finnish, Norwegian, German and North American, the relationship between the CYP1A1*2A allele and lung cancer was not observed (Tefre et al, 1991;Hirvonen et al, 1992;Shields et al, 1993;Drakoulis et al, 1994).…”
mentioning
confidence: 99%